Analysis of factors influencing students' participation in national and international competitions - Setia, Putri Bunga; Kurniawan, Andre; Indrawan, Eko; Wulansari, Rizky Ema; Kassymova, Gulzhaina Kuralbayevna (Universitas Negeri Padang, 2025)
Higher education plays an important role in preparing students to become competent and competitive individuals. Furthermore, participating in academic competitions is a strategic means to foster innovative, collaborative, and competitive skills. This study employed Structural Equation Modeling (SEM) using Smart PLS (Partial Least Squares) software, a statistical technique suitable for analyzing complex relationships between variables. The analysis process involved two stages: measurement model and structural model. The analysis showed that the T-statistic for peer influence was 2.549, exceeding the threshold of 1.96, with a p-value of 0.011, below the 0.05 threshold for statistical significance. Similarly, the T-statistic for family influence was 3.803, also exceeding 1.96, with a p-value of 0.000, indicating a highly significant relationship. These findings highlight the important role of external factors, especially peer and family influence, in motivating students to participate in national and international competitions. Therefore, educational institutions need to implement targeted strategies to increase students’ motivation and encourage active involvement in these competitions.